Library Outreach and Instruction to Academic Departments of Military Science and ROTC Cadets. Issue 2 (3rd July 2017) - Rod-Welch, Leila June; Weeg, Barbara E.; Keith, Glen P.
ABSTRACT: Colleges and universities across the United States have seen increases in the number of students of traditional college age choosing to enter college and the Army Reserve Officers' Training Corps (ROTC) simultaneously to attain college degrees and begin their military careers. ROTC students, cadets, will benefit from knowledge of library services and resources and from specialized library outreach and instruction. Librarians who understand the military system and culture, and who examine their own attitudes toward military service, will be better prepared to work with military science faculty and ROTC cadets. The outreach session to the Department of Military Science/ROTC and the one-session library instruction provided to ROTC cadets by librarians at a Midwestern, comprehensive university are described and assessed.